CXCR4 as biomarker for radioresistant cancer stem cells. (August 2014) - Trautmann, Franziska; Cojoc, Monica; Kurth, Ina; Melin, Nicolas; Bouchez, Laure C.; Dubrovska, Anna; Peitzsch, Claudia
Abstract Purpose: Radioresistance of cancer cells remains a fundamental barrier for maximum efficient radiotherapy. Tumor heterogeneity and the existence of distinct cell subpopulations exhibiting different genotypes and biological behaviors raise difficulties to eradicate all tumorigenic cells. Recent evidence indicates that a distinct population of tumor cells, called cancer stem cells (CSC), is involved in tumor initiation and recurrence and is a putative cause of tumor radioresistance. There is an urgent need to identify the intrinsic molecular mechanisms regulating the generation and maintenance of resistance to radiotherapy, especially within the CSC subset. The chemokine C-X-C motif receptor 4 (CXCR4) has been found to be a prognostic marker in various types of cancer, being involved in chemotaxis, stemness and drug resistance. The interaction of CXCR4 with its ligand, the chemokine C-X-C motif ligand 12 (CXCL12), plays an important role in modulating the tumor microenvironment, angiogenesis and CSC niche. Moreover, the therapeutic inhibition of the CXCR4/CXCL12 signaling pathway is sensitizing the malignant cells to conventional anti-cancer therapy. Content: Within this review we are summarizing the role of the CXCR4/CXCL12 axis in the modulation of CSC properties, the regulation of the tumor microenvironment in response to irradiation, therapy resistance and tumor relapse. Conclusion: In light of recent findings, the inhibition of the CXCR4/CXCL12 signaling pathway is a promising therapeutic option to refine radiotherapy.